A study of rhetorical devices in love song titles in English versus Vietnamese - Nguyễn, Thị Minh Nguyệt. (The University of Da Nang, 2015)
This thesis is conducted to investigate some commonly used rhetorical devices; point out their similarities, differences and their frequencies of occurrence in English and Vietnamese love song titles. The data of the study were collected from songbooks and music websites in English and Vietnamese. The data were described and contrastively analyzed on stylistic aspects under qualitative and quantitative approaches to yield more precise points on rhetorical devices in English and Vietnamese love song titles. On the basis of a contrastive analysis, the thesis tries to find out some commonly used rhetorical devices in English and Vietnamese love song titles, namely metaphor, metonymy, simile, personification, and rhetorical questions. With an eye to partly contributing to better teaching and learning English as a foreign language, specifically to better the awareness of learners in translating and writing songs, some suggested ideas are also included.